Influence of rectification procedure on the counter-torque force of prosthetic screws of implant-retained frameworks - Mauro Antonio de Arruda Nobilo; Guilherme Elias Pessanha Henrique; Wagner Sotero Fragoso; Ana Carolina Masarolo Machado; Luiz Gustavo Dias Daroz; Marcelo Ferraz Mesquita (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the counter-force of prosthetic screws before and after the rectification procedure of the seating base of prosthetic framework screws. Methods: With a metal matrix containing three replicas of conical abutments (Micro-Unit; Conexão) placed at 10 mm from center to center, ten multiple cast structures were made of a titanium monoblock. The multiple cast structures were fastened onto the metal matrix abutments with a torque of 10 NCm. The screwing sequence was performed from the central pillar towards the distal ones. The force (Ncm)necessary for counter-torque was evaluated using a digital torque meter (TQ3000; Lutron, Taipei, Taiwan). This procedure was carried out before and after rectification of the seating base of the prosthetic screws, by means of a manual rectifier tip (Conexão Sistemas de Prótese, São Paulo, Brazil). The mean counter-torque values were calculated for each structure before and after rectification. The t-Test for paired samples was used to compare the evaluated situations. Results: Significant difference was observed between the mean counter-torque force value of the prosthetic screws before (5.78±1.03Ncm) and after (7.06±0.62Ncm) the rectification procedures (p<0.01). Conclusion: The rectifying process of the seating base significantly increased the values of force required to counter-torque the prosthetic screws of cast implant-retained multiple frameworks.